Hermeneutics Of Social Interaction Relations In Islam - Amin, Surahman; Rasid, Ruslan (International Journal of Educational Research & Social Sciences, 2023)
This study examines how social interaction in Islam is then able to give an attitude of tolerance among religious people, especially contained in Q.S Al-Baqarah/2:120 and Q.S Al-Fath/48:29.The methodology used in this study is Hans Georg Gadamer's hermeneutics with Tashihiko's semantic approach. The aim is to "get a different understanding of the monotonous and textual interpretation as is the understanding of most Muslims of the two verses so that these two verses can be understood as verses of religious moderation. The results of the study stated that: First, Islam as a religion of mercy always invites its people to build an attitude of tolerance towardanyone and remain vigilant, firm, and courageous. Second, in the hermeneuticsemantic view, these two verses are better understood as motivational verses so that they cannot be interpreted as verses that legalize violence and hatred against other than Islam. Third, lafadz asyidda in Q.S. Al-Fath/48:29 contains other meanings besides meaning violence, in this research lafadz asyidda also has its own meaning, including firmness, firmness here is certainly measured by how much tolerance level a person has, the environment and globally. Fourth, the two verses above contain the meaning as a form of consistency and upholding "the value of justice in social society. Therefore, the researcher understands that the two verses above are a reinterpretation of the understanding of "most people that the two verses above are verses inciting hatred and hostility towards "other than Islam".